Analisis Rasio Keuangan Bank Pembangunan Daerah di Indonesia (Studi Empiris pada Bank Jambi Periode 2017 s/d 2019) - Osi, Indah; Prayitno, Sugeng; Wiarta, Iqra; Kurniasih, Endah Tri (Universitas Batanghari, 2020)
The regional development bank is part of the financial services industry in Indonesia. Regional development banks in addition to intermediation in the financial system also have an important role for the region, namely as a source of income for the region. That is why a good asset quality assessment is required in order for the regional development bank to provide dividends and survive in the financial services industry. This research aims to find out and analyze the asset quality of regional development banks in Indonesia with case studies on jambi regional development bank or commonly abbreviated jambi bank. The research method used is quantitative analysis with sourced in secondary data taken from the annual report of Jambi bank for the period 2017 to 2019 with an assessment of the assessment of bank Indonesia regulation number 14/15/PBI/2012. The results of the study are capital ratio, asset quality, rentability and liquidity of jambi banks as a whole to achieve a good ratio in the period 2017 to 2019.